Impact of COVID-19 pandemic on therapy in cancer patients - Szklener, Katarzyna; Rodzajewska, Anna; Kuryło, Weronika; Mańdziuk, Sławomir (Journal of Education, Health and Sport, 2022)
Introduction and purpose: The Covid-19 pandemic has spread rapidly across the globe, resulting in more than 6 million deaths worldwide. Oncological patients are considered to be at increased risk of SARS-CoV-2 coronavirus infection and the severe course of the disease. The current understanding of the correlation between COVID-19 and cancer is limited. In this study, we attempted to analyze the course of SARS-CoV-2 infection in cancer patients who were treated at the Department of Clinical Oncology and Chemotherapy SPSK4 in Lublin in the period from November 2020 to March 2022. Material and methods: This retrospective study included patients in the age rage from 36–79 years old. All necessary information were obtained from electronic medical records. Subsequently collected data were submitted to statistical calculations. Results: A varied course of COVID-19 infection in oncology patients has been observed. Preliminary observations showed that, in many cases COVID-19 infection caused a delay in the administration of the next dose of a therapeutic agent during the course of systemic anticancer treatment, but this delay was not observed to have a significant impact on reducing the effectiveness of oncology treatment Conclusions: In the light of our own presented observations, global statistics and reports of other authors, the role of certain individual characteristics of patients is visible, which increase the risk of more severe course of SARS-CoV-2 infection and / or increased mortality . It is necessary to continue the search for an optimal diagnostic regimen that would identify cancer patients with a particular risk of the most severe complications of SARS-CoV-2 infection.